2008
DOI: 10.1371/journal.pone.0001589
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Proteomic Analysis Suggests that First L-Dopa Dose Equates to Chronic Exposure

Abstract: L-3,4-dihydroxypheylalanine (L-dopa)-induced dyskinesia represent a debilitating complication of therapy for Parkinson's disease (PD) that result from a progressive sensitization through repeated L-dopa exposures. The MPTP macaque model was used to study the proteome in dopamine-depleted striatum with and without subsequent acute and chronic L-dopa treatment using two-dimensional difference in-gel electrophoresis (2D-DIGE) and mass spectrometry. The present data suggest that the dopamine-depleted striatum is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 57 publications
(88 reference statements)
3
34
0
Order By: Relevance
“…These observations were supported by quantitative immunoelectron microscopy data from 6-OHDA-treated rats showing a significant decrease in the number of striatal D1-negative spines (Day et al, 2006). A recent electron microscopy study using a non-stereologic spine count method showed a relative decrease in the number of D2-immunopositive spines accompanied with an increase in the number of D1-immunoreactive spines in a MPTP-treated monkey model of PD (Scholz et al, 2008). On the other hand, these observations are different from those in a large number of Golgi studies in both human parkinsonians and animal models of parkinsonism showing a rather homogeneous loss of spines across large populations of Golgi-impregnated striatal medium spiny neurons (Ingham et al, 1989; Stephens et al, 2005; Zaja-Milatovic et al, 2005; Villalba et al, 2009; Smith et al, 2009b).…”
Section: - Striatal Spine Pathogenesis In Parkinson’s Disease Versumentioning
confidence: 99%
“…These observations were supported by quantitative immunoelectron microscopy data from 6-OHDA-treated rats showing a significant decrease in the number of striatal D1-negative spines (Day et al, 2006). A recent electron microscopy study using a non-stereologic spine count method showed a relative decrease in the number of D2-immunopositive spines accompanied with an increase in the number of D1-immunoreactive spines in a MPTP-treated monkey model of PD (Scholz et al, 2008). On the other hand, these observations are different from those in a large number of Golgi studies in both human parkinsonians and animal models of parkinsonism showing a rather homogeneous loss of spines across large populations of Golgi-impregnated striatal medium spiny neurons (Ingham et al, 1989; Stephens et al, 2005; Zaja-Milatovic et al, 2005; Villalba et al, 2009; Smith et al, 2009b).…”
Section: - Striatal Spine Pathogenesis In Parkinson’s Disease Versumentioning
confidence: 99%
“…The introduction of mass spectrometry to the field of comprehensive protein analysis, termed proteomics, has advanced the field significantly because MS offers high specificity while being relative time and cost effective. The only two proteomic studies published so far on LID and PD employed two dimensional-differential gel electrophoresis (2D-DIGE), but because of limitation concerning analysis of low molecular weight compounds (Ͻ5 kDa), gel electrophoresis based proteomic studies do not permit the analysis of endogenous neuropeptides, such as the fully processed opioid peptides (53,54). Furthermore, neuropeptide levels are often present in low amounts in the femtomolar range beyond the limits of detection of gel-based proteomics (55).…”
Section: Detection Of Other Dynorphin Related Peptides-several Dynorpmentioning
confidence: 99%
“…Proteomic techniques allow complex biology especially as they relate to disease processes, making it possible to unravel the basis of LID manifestation in the DA-depleted brain. To fill this void, the MPTP macaque model was used to study the proteome in DA-depleted striatum with and without subsequent acute and chronic L-dopa treatment using two-dimensional difference in-gel electrophoresis and mass spectrometry (Kultima et al , 2006; Scholz et al , 2008). Interestingly, the experimental design included control monkeys, untreated parkinsonian monkeys, parkinsonian monkeys treated for the first time ever that did not exhibit dyskinesia at the peak of the antiparkinsonian effect, and parkinsonian monkeys chronically-treated with L-dopa for months and displaying overt dyskinesia at the peak of the antiparkinsonian effect (Scholz et al , 2008).…”
Section: Pathophysiology Of Da-depleted and Daergic Drug First-evementioning
confidence: 99%